For the love of shoes - Farameh, Patrice; Stephenson, Mary Alice; Steele, Valerie; Benasra, Julie (Kempen, Germany : teNeues, 2013)
Women have long realized that cool shoes do not only complement the outfit, they are the whole point. From Cinderella to Carrie, we have all fallen head over heels for the right pair-and to hell with cost or comfort! This book explores the outer realms of avant-garde shoe design. Unfettered by commercialism, these pioneering designers give full rein to their artistic visions. These zany pieces contain an array of extraordinary forms and materials. With influences ranging from Las Vegas pizzazz and arcane tribal relics to contemporary architecture, it may be difficult to distinguish between fun footwear and conceptual sculpture. Shoe designers include: Manolo Blahnik, Alexa Wagner, Camilla Skovgaard, Laurence Dacade, Marloes Ten Bhömer, Alexander McQueen, Casadei, Stuart Weitzman, Chau Har Lee, Charlotte Olympia, Naim Josefi, Netta Makkonen, Christian Louboutin, Daniele Michetti, Diego Dolcini, Edmundo Castillo, Gio Diev, Stubbs & Wootton, Jerome C. Rousseau, Jimmy Choo, Gina, Lauren Tennenbaum, Omar Angel Perez, Pauline Van Dongen, Pour La Victoire, Noritaka Tatehana, DSquared² and others.
Includes texts: Little pleasures by Patrice Faramed, The Stylist by Mary Alice Stephenson, The Shoe Obsession by Dr. Valerie Steele and God Save My Shoes by Julie Benasra.
boek
Keywords: Shoes -- History -- 21st century; Shoes -- History -- 20th century; Women's shoes -- Design; Women's shoes -- Pictorial works; Fashion designers -- Biography; Accessoire; Schuh